Impacto de los movimientos repetitivos y su relación con los trastornos osteomusculares en miembro superior en trabajadores de la empresa florícola "La Herradura". Diseño de un sistema de gestión. - Valencia Naveda, Miryan Patricia (2015)
This investigation aims to design a Management System for Occupational Health area Cultivation and Floriculture Postharvest company La Herradura. It was identified in the medical department of the company increased musculoskeletal diseases, mainly in upper limb affecting cultivation and postharvest workers who have been registered two cases of occupational disease problem behind this research. Using statistical methods and the application of a test worker with early symptoms identified with 60% incidence. The test includes various symptoms of diseases of superior limb, at different heights of the anatomical structures that are affected by the characteristics of the job. The management system was designed based on protocols in order to provide a tool for controlling ergonomic risk factor. The development of the Management System for Occupational Health for the Postharvest and crop area to improve the quality of life of workers. Therefore it concludes that the system is a basic tool for all types of organization that seeks to improve the quality and continuous improvement. The implementation of the Management System of Occupational Health in the company La Herradura is recommended.